Analyzing ovarian tumor and cancer cells using image processing algorithms K means & fuzzy C-means - N G, Thangamma; S. Prasanna, Dr (International Journal of Engineering and Technology, 2018)
Ovarian growth is a tumor that occurs in the ovaries of the women. Sometimes, it may derive to be a malignant tumor. Those tumors are acute cancer cells that could be life-threatening if the treatment had not been properly taken. Few of the cases, malignant tumors can be re-moved using surgery or by means of radiations..There is a chance of cancer if not properly removed and they could grow back. Analyzing ovarian cancer is found to be the highest mortality rate of all categories of cancers affecting the women. Considering its malignant effect necessary remedial actions need to be carried out for the welfare of the peoples in the future. Researches and various analysis are being car-ried out to overcome the drastic effect of malignant tumor. Supporting the research, in this paper we have analyzed various imaging modali-ties to examine segmentation and texture analysis with the help of K-Means and Fuzzy C-Means.Â Â